Management of vaccination - related anaphylaxis - Harsono, Ariyanto (Paediatrica Indonesiana, 2001)
Anaphylaxis is a systemic, immediate hypersensitivity reaction due to IgE mediated immunologic release of mediators from mast cells and basophils. Features of severe condition are obstruction of the upper airway from tissue swelling, marked bronchospasm, and hypotension. In vaccination related anaphylaxis, optimal management begins with prevention: prevaccination screening including questions about possible allergy to any component of vaccine, and anticipation of anaphylaxis by observation at least 15 minutes following vaccination are very important. The essential treatment is prompt administration of adrenaline. Since hypotension is due to a shift of fluid from intravascular to extravascular space, the mainstay of treatment should be the restoration of intravascular volume. Since anaphylaxis can be biphasic administration of corticosteroid in preventing late phase reaction can be postulated.